Synthesis and Characterization of One-Component Polymeric Photoinitiator by Simultaneous Double Click Reactions and Its Use in Photoinduced Free Radical Polymerization - Temel, Gokhan; Aydogan, Binnur; Arsu, Nergis; Yagci, Yusuf (AMER CHEMICAL SOC, 2009)
A polystyrene copolymer (PS-B-DMAB) possessing both benzophenone and dimethylamino moieties in the side chain was synthesized by a combination of nitroxide-mediated radical polymerization (NMRP) and simultaneous double click reactions. First, a random copolymer of styrene (S) and chloromethyl styrene (CMS) with 32 mol % CMS content was prepared by NMRP process. Then, chloromethyl groups were converted to azide groups by reacting with NaN3 in DMF. The other two click components, namely, propargyl benzophenone (Pr-B) and propargyl 4-(dimethylamino)benzoate (Pr-DMAB), were prepared independently by the etherification and esterification reactions, respectively. Then, in the final stage, the obtained alkyne functional chromophoric (Pr-B) and hydrogen-donating (Pr-DMAB) molecules were anchored to azide-modified polystyrene (PS-N-3) in one-step by click chemistry. The final polymer (PS-B-DMAB) and the intermediates were characterized in detail by spectral analysis and laser flash photolysis studies. The resulting polymer possesses absorption characteristics similar to bare bezophenone. The one-component photoinitiating nature of PS-B-DMAB was demonstrated by photopolymerization of mono- and multifunctional monomers, namely, methyl methacrylate (MMA) and trimethylolpropane triacrylate (TMPTA), respectively.
Keywords: CE(IV)/HNO3 REDOX SYSTEM; SIDE-CHAIN THIOXANTHONE; DENDRONIZED LINEAR-POLYMERS; ONE-POT SYNTHESIS; DIELS-ALDER; MIDCHAIN MACROPHOTOINITIATOR; COINITIATOR AMINE; BLOCK-COPOLYMERS; 1,3-DIPOLAR CYCLOADDITIONS; FUNCTIONALIZED POLYMERS; Polymer Science